The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12864-018-5048-4
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of the promoter region of bnip3 and bnip3l genes induced by metabolic programming

Abstract: BackgroundEnvironmental changes of biotic or abiotic nature during critical periods of early development may exert a profound influence on physiological functions later in life. This process, named developmental programming can also be driven through parental nutrition. At molecular level, epigenetic modifications are the most likely candidate for persistent modulation of genes expression in later life.ResultsIn order to investigate epigenetic modifications induced by programming in rainbow trout, we focused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 72 publications
0
24
0
2
Order By: Relevance
“…As such, methionine potentially represents a critical factor in nutritional programming. In this regard, we recently reported that feeding a methionine-deficient diet to rainbow trout broodstock for 6 months affected the activation and/or expression of several key metabolic factors in offspring through DNA methylation (Veron et al, 2018), confirming the possibility of nutritional programming in fish through parental methionine nutrition (Fontagné-Dicharry et al, 2017;Seiliez et al, 2017).…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…As such, methionine potentially represents a critical factor in nutritional programming. In this regard, we recently reported that feeding a methionine-deficient diet to rainbow trout broodstock for 6 months affected the activation and/or expression of several key metabolic factors in offspring through DNA methylation (Veron et al, 2018), confirming the possibility of nutritional programming in fish through parental methionine nutrition (Fontagné-Dicharry et al, 2017;Seiliez et al, 2017).…”
Section: Introductionmentioning
confidence: 71%
“…This finding is supported by several studies which demonstrated that early imbalanced dietary methionine led to modulation of DNA and histone methylation later in life through the control of the one-carbon metabolism (Rees, 2002;Waterland, 2006;Waterland and Jirtle, 2004). Recently, we also reported that for both broodstock and early fry, methionine nutrition affected the methylation of several CpG sites and the mRNA levels of bnip3a (bcl-2/E1B-19K interacting protein 3) and bnip3lb1 (also known as nix) genes involved in mitochondrial mediated apoptosis and/or mitophagy (Veron et al, 2018). In the present study, we did not observe any modulation of global DNA methylation in the livers of fish from fry fed the MD diet compared with their control counterparts.…”
Section: Bmentioning
confidence: 83%
See 1 more Smart Citation
“…At the same time, more proximal CpG islands in mice showed no variation [45]. This seems not unusual, as studying the possibility to program the response to hypoxia and dietary methionine deficiencies in rainbow trout, it was observed that the methylation level of targeted genes was consistently low (0 to 3%) in proximal positions (until -600 bp), being more susceptible to be methylated the CpG sites at more distal positions [53].…”
Section: Fish Scd1a Can Be Programed Through Broodstock Nutritionmentioning
confidence: 88%
“…Different studies in fish have revealed how the early environment can have long lasting-effects on the later phenotype and on the ability to adapt to environmental conditions later in life (reviewed by [50]). Such early stimuli refer, among others, to temperature at larval stage [51], cold-shock and air-exposure to embryos and larvae [52], early acute hypoxia at embryo stage, broodstock or fry methionine deficient diets [53], and first feeding with carbohydrates [54], a mix of plant proteins [55] or soya-based diets [56,57]. There is also experimental evidence for the nutritional programing of lipid metabolism in both fish [20,38,39,40,41,42], and higher vertebrates [48,49], though the epigenetic mechanisms regulating the expression of key genes such as fads2 and scd1 remains elusive in fish, and in marine fish in particular.…”
Section: Discussionmentioning
confidence: 99%